Annual Plan 1994-95 Volume-III V. Energy; VI. Industry and Minerals General Areas Government of Assam - Planning Commission (Planning Commission, 1994)
The Geological Survey of India (G.S.I) and the Geology and Mining Department of the State Government have been carrying out extensive surveys on the mineral resources of the State. Such surveys have revealed deposits of coal, mineral/fossil oil, natural gas, limestone, granite, clay, iron-ores, Fuller's earth etc., but no worthwhile utilisation has been made of these materials except coal, mineral oil and natural gas as their occurrences are sporadic and economic viability of some are yet to be established Search work for these minerals in the State requires added efforts.
Government of Assam, Planning and Development Department